2020
DOI: 10.3390/app10186402
|View full text |Cite
|
Sign up to set email alerts
|

The BrIdge voLcanic LIdar—BILLI: A Review of Data Collection and Processing Techniques in the Italian Most Hazardous Volcanic Areas

Abstract: Volcanologists have demonstrated that carbon dioxide (CO2) fluxes are precursors of volcanic eruptions. Controlling volcanic gases and, in particular, the CO2 flux, is technically challenging, but we can retrieve useful information from magmatic/geological process studies for the mitigation of volcanic hazards including air traffic security. Existing techniques used to probe volcanic gas fluxes have severe limitations such as the requirement of near-vent in situ measurements, which is unsafe for operators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(206 reference statements)
0
1
0
Order By: Relevance
“…In volcanic areas, gases represent important physical evidence of volcanic processes that need to be measured. Parracino et al [9] have shown how novel range-resolved DIAL-Lidar (Differential Absorption Light Detection and Ranging) could herald a new era in the observation of long-term volcanic CO 2 gases.…”
mentioning
confidence: 99%
“…In volcanic areas, gases represent important physical evidence of volcanic processes that need to be measured. Parracino et al [9] have shown how novel range-resolved DIAL-Lidar (Differential Absorption Light Detection and Ranging) could herald a new era in the observation of long-term volcanic CO 2 gases.…”
mentioning
confidence: 99%